PROMOSI KESEHATAN DENGAN PEMBERIAN REBUSAN DAUN SELEDRI UNTUK MENURUNKAN TEKANAN DARAH PADA WANITA MENOPAUSE - Diah Evawanna Anuhgera; Riris Sitorus; Nikmah Jalilah Ritonga; Juni Mariati Simarmata; Novita Br Ginting Munthe (JURNAL PENGMAS KESTRA (JPK), 2021)
Abstract Hypertension is a chronic disease that often results in complications for other organs. Based on the findings of recent evidence that giving celery leaf decoction can lower blood pressure. Health promotion activities through the provision of celery leaf stew can be used as an alternative in promoting early prevention and treatment of hypertension cases that often occur in menopausal women. The goal of this community service is to improve the quality of life of menopausal women by helping to lower blood pressure non-pharmacologically and reducing the side effects felt in women with hypertension. Celery leaves stew can be given once a day on a regular basis. The implementation of this community service lasted for 2 days at the Head Office of Sidodadi Ramunia Village, Beringin Deli Serdang District. This activity begins with conducting a rapid test for all respondents, followed by a blood pressure check before the promotion of the activity. On the second day of implementation, each respondent took blood pressure measurements to see the decrease in blood pressure for each respondent. The results of blood pressure examinations from 32 respondents showed a decrease in sysitolic blood pressure by 32 people (100%) and a decrease in diastolic blood pressure by 28 people (81.25%). Celery leaves decoction can be useful for hypertensive women to lower and control blood pressure. Keywords: health promotion, celery leaves, blood pressure, hypertension